Predictors of Early Failure After Fecal Microbiota Transplantation for the Therapy of Clostridium Difficile Infection: A Multicenter Study. (July 2016) - Fischer, Monika; Kao, Dina; Mehta, Shama R; Martin, Tracey; Dimitry, Joseph; Keshteli, Ammar H; Cook, Gwendolyn K; Phelps, Emmalee; Sipe, Brian W; Xu, Huiping; Kelly, Colleen R
Abstract : OBJECTIVES: Fecal microbiota transplant (FMT) is a highly efficacious treatment for recurrent or refractory Clostridium difficile infection (CDI); however, 10–20% of patients fail to achieve cure after a single FMT. The aim of this study was to identify risk factors associated with FMT failure and to develop and validate a prediction model for FMT failure. METHODS: Patient characteristics, CDI history, FMT characteristics, and outcomes data for patients treated between 2011 and 2015 at three academic tertiary referral centers were prospectively collected. Early FMT failure was defined as non‐response or recurrence of diarrhea associated with positive stool C. difficile toxin or PCR within 1 month of FMT. Late FMT failure was defined as recurrence of diarrhea associated with positive stool C. difficile toxin or PCR between 1 and 3 months of the FMT. Patient data from two centers were used to determine independent predictors of FMT failure and to build a prediction model. A risk index was constructed based on coefficients of final predictors. The patient cohort from the third center was used to validate the prediction model. RESULTS: Of 328 patients in the developmental cohort, 73.5% ( N =241) were females with a mean age of 61.4±19.3 years; 19.2% ( N =63) had inflammatory bowel disease (IBD), and 23.5% ( N =77) were immunocompromised. The indication for FMT was recurrent CDI in 87.2% ( N =286) and severe or severe‐complicated in 12.8% ( N =42). FMT was performed as an inpatient in 16.7% ( N =54). The stool source was patient‐directed donors in 40% ( N =130) of cases. The early FMT failure rate was 18.6%, and the late failure rate was 2.7%. In the multivariable analysis, predictors of early FMT failure included severe or severe‐complicated CDI (odds ratio (OR) 5.95, 95% confidence interval (CI): 2.26–15.62), inpatient status during FMT (OR 3.78, 95% CI: 1.55–9.24), and previous CDI‐related hospitalization (OR 1.43, 95% CI: 1.18–1.75); with each additional hospitalization, the odds of failure increased by 43%. Risk scores ranged from 0 to 13, with 0 indicating low risk, 1–2 indicating moderate risk, and ≥3 indicating high risk. In the developmental cohort, early FMT failure rates were 5.6% for low risk, 12.7% for moderate risk, and 41% for high‐risk patients. Of 134 patients in the validation cohort, 57% ( N =77) were females with a mean age of 66±18.1 years; 9.7% ( N =13) had IBD, and 17.9% ( N =24) were immunocompromised. The early FMT failure rate at 1 month was 19.4%, with an additional 3% failing by 3 months. In the validation cohort, FMT failure rates were 2.1% for low risk, 16.1% for moderate risk, and 35.7% for high risk patients. The area under the receiver operating characteristic curve (AUROC) for FMT failure was 0.81 in the developmental cohort and 0.84 in the validation cohort. CONCLUSIONS: Severe and severe‐complicated indication, inpatient status during FMT, and the number of previous CDI‐related hospitalizations are strongly associated with early failure of a single FMT for CDI. The novel prediction model has good discriminative power at identifying individuals who are at high risk of failure after FMT therapy and may assist the treating physician in subsequent management plans.